The Effect Of Number Of Excitation (Nex) Variation And Blade Technique On T2 Image Quality TSE Sagital Knee MRI - Fella Ustia Nirmala (Universitas Airlangga, 2019)
ABSTRACT The research has been conducted entitled Influence of Variation Number of Excitation (NEX) and BLADE Technique on Image Quality T2 TSE Sagital Knee MRI. This research was conducted at Haji General Hospital Surabaya by using MRI 1.5 Tesla modalities. The usage of BLADE technique combined with the NEX 1 and NEX 2 variations performed on sagittal tissue of the knee and using a Turbo Spin Echo (TSE) sequence with T2 weighting. Data analysis was done quantitatively by using Region of Interest (ROI) method on MRI computer then analyzed Sinyal to Noise Ratio (SNR) and Contrast to Noise Ratio (CNR). From the research, good image quality result obtained by using BLADE technique on NEX 2 variation with SNR of tissues was 130,71 for Fluid, 5,54 for Meniscus, 12,88 for Anterior Cruciate Ligament (ACL) and 5,95 for Posterior Cruciate Ligament (PCL), whereas the CNR value of tissues was 125.16 for fluid-meniscus, 117.82 for ACL-fluid and 124.76 for fluid-PCL. Keywords : NEX , TSE, T2 weighting, MRI Knee.